PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN TEAM WORK DALAM MENINGKATKAN KINERJA KARYAWAN PT. MITRA UNTUNG SEJAHTERA - Mukhbit Al Yaafi; Vera Firdaus; Dewi Andriani (LPPM STIE Muhammadiah Bandung, 2025)
The purpose of this study was to determine how a supportive work environment, effective team collaboration, and the application of transformational leadership style correlate with employee motivation and productivity. This type of research uses a quantitative descriptive research approach. The population used was 150 employees of PT. Mitra Untung Sejahtera aged over 21 years. The sampling technique used was purposive sampling. The location of the study was in Ketegan Village, Tanggulangin District, Sidoarjo Regency. The data obtained will then be processed using the SmartPLS 4 program. The results of the study are that leadership, work environment and teamwork have a significant positive effect on employee performance.